2009
DOI: 10.3941/jrcr.v3i4.169
|View full text |Cite
|
Sign up to set email alerts
|

Cemento-ossifying Fibroma Of Paranasal Sinus Presenting Acutely As Orbital Cellulitis

Abstract: Fibro-osseous lesions of the face and paranasal sinuses are relatively uncommon. These lesions have overlapping clinical, radiologic and pathologic features causing difficulty in diagnosis. Neoplastic fibro-osseous paranasal sinus lesions can be benign or malignant. The benign fibro-osseous lesions described are: ossifying fibroma (and its histologic variants) and fibrous dysplasia. The variants of ossifying fibroma differ in the nature of calcified material (i.e. cementum versus bone), in the location of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…2 In our study, COFs frequently showed homogeneous groundglass appearance similar to that observed in fibrous dysplasia [five of eight (63%)]; however, large COFs may appear as heterogeneous masses. 2,10,11 The relatively small size of COFs in our study [mean maximum diameter, 20.3 mm (range, 7-33 mm)] may have affected the intratumoral homogeneity.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…2 In our study, COFs frequently showed homogeneous groundglass appearance similar to that observed in fibrous dysplasia [five of eight (63%)]; however, large COFs may appear as heterogeneous masses. 2,10,11 The relatively small size of COFs in our study [mean maximum diameter, 20.3 mm (range, 7-33 mm)] may have affected the intratumoral homogeneity.…”
Section: Discussionmentioning
confidence: 79%
“…Indeed, fluid-fluid levels have been reported in OFs with secondary aneurysmal bone cysts. 8,10,[13][14][15][16] In a study, 15 out of 438 (3.42%) patients with OFs in the paranasal sinus showed fluid-fluid levels; the histological subtypes included COF in 10 patients (66.7%), JPOF in 4 (26.7%), and JTOF in 1 (6.7%). 13 However, in our study, fluid-fluid level was not observed in any OF.…”
Section: Discussionmentioning
confidence: 99%
“…As the lesion matures, there are increasing calcific flecks progressing to a radio opaque mass. [15] This case manifested as a well circumscribed radiolucent lesion with internal radiopacities and root resorption was also noted. CT image revealed an osteolytic lesion with the expansion of bucco-lingual cortices and there was no cortical violation.…”
Section: Discussionmentioning
confidence: 85%